Type 2 diabetes mellitus and hypertension as predictors of community-acquired pneumonia in Peruvian older adults with cancer - Moncada-Mapelli, Enrique (2023)
Objective: To evaluate DM2 and hypertension as predictors of CAP in older adults with cancer. Material and Methods: We conducted a secondary data analysis of a prospective cohort study in older adults with cancer from the Geriatrics Service of the Centro Médico Naval (CEMENA) of Peru during 2013-2015. T2DM and hypertension diagnosis were obtained from medical records. CAP was defined according to clinical and radiological diagnostic criteria and it was collected from the medical records of the patients up to one year after their inclusion in the study. We used the statistical software STATA v14.0 to develop the analysis. We performed multivariate analysis using crude and adjusted Cox regression models. The reported measure was the hazard ratio (HR) with their respective 95% confidence intervals (95%CI). Results: A total of 231 older adults with cancer were analyzed. The mean age of the participants was 78.6 ± 4.2 (range: 74-92 years) and all of them were men. 33 (14.29%) patients developed CAP during the follow-up, 53 (21.65%) had hypertension, and 56 (22.65%) T2DM. CAP was more frequent in patients with lung cancer and lymphomas. In the adjusted Cox regression models, we found T2DM (aHR=1.49; 95%CI: 1.21-1.79) and hypertension (aHR=1.32; 95%CI: 1.24-1.50) were predictors of CAP incidence. Conclusion: T2DM and hypertension were associated with CAP incidence in oncogeriatric patients. Future intervention studies are needed to improve the functionality and prevent CAP in this vulnerable population